The Different Uses of the Term Παρρησία by John Chrysostom in the Corpus Paulinum - Willigen, M. A. van (Journal of early Christian history, 2024)
Chrysostom, in his sermons on the letters of Paul, explains the term παρρησία in different ways. These different explanations correspond for the most part with the definition of παρρησία as given by Foucault, but contain more nuances than his definition indicates. This article describes and analyses the breadth of meaning of the word and highlights three aspects: (1) The use of παρρησία by Paul and John Chrysostom in the corpus Paulinum, (2) the function of this use, and (3) the psychological and anagogical aspects of John Chrysostom’s paraenesis, in which παρρησία plays an important role. Chrysostom knows the Pauline use of the term well, respects it and very often adopts it. Moreover, he uses the term as an important stimulus to activate his listeners in a spiritual, anagogical way. Using παρρησία in the relationship to God, especially at the judgement on the last day and being wholeheartedly prepared to apply παρρησία in the proclamation of the gospel is crucial for Chrysostom. He presents both very positively to listeners and as an essential characteristic of a sincere Christian’s identity. In many cases, Chrysostom insists on this παρρησία and urges believers to use it precisely in their contact with God in prayer. Chrysostom connects παρρησία in a direct way with innocence and sincerity. Believers can have παρρησία when they are sincere before God and show mercy to their fellow human beings. In their dealings with their fellow human beings, Christians should practice humility, ταπϵινοϕροσύνη and πραύτης, according to Chrysostom.